2017
DOI: 10.1021/acsomega.7b01181
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation of Fatty Acids with Triruthenium Dodecacarbonyl: Influence of the Compound Structure and Analysis of the Product Mixtures

Abstract: Recently, the decarboxylation of oleic acid (9( Z )-octadecenoic acid) catalyzed by triruthenium dodecacarbonyl, Ru 3 (CO) 12 , to give a mixture of heptadecenes with concomitant formation of other hydrocarbons, heptadecane and C17 alkylbenzenes, was reported. The product mixture, consisting of about 77% heptadecene isomers, 18% heptadecane, and slightly >4% C17 alkylbenzenes, possesses acceptable diesel fuel properties. This reaction is now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 45 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…It has already been shown that neat furanacrylic acid will undergo decarboxylation to 2‐vinylfuran, albeit at much higher temperature, by heating at 300–320 °C in a tube furnace (Moureu et al, ; Wagner, ). Although these decarboxylated 2‐ n ‐alkenylfurans were obtained in low yield, the conditions for their formation were rather mild in contradistinction with those effecting decarboxylation of fatty acids (transition metals, >300 °C) (Fu et al, ; Knothe et al, ; Mohite et al, ; Wu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…It has already been shown that neat furanacrylic acid will undergo decarboxylation to 2‐vinylfuran, albeit at much higher temperature, by heating at 300–320 °C in a tube furnace (Moureu et al, ; Wagner, ). Although these decarboxylated 2‐ n ‐alkenylfurans were obtained in low yield, the conditions for their formation were rather mild in contradistinction with those effecting decarboxylation of fatty acids (transition metals, >300 °C) (Fu et al, ; Knothe et al, ; Mohite et al, ; Wu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moser et al (2016) further reported that 77.6% heptadecene and 18.0% heptadecane was obtained by Ru-catalyzed DCX/DCN of fatty acids. There were also other reactions such as the decarboxylation, dehydrogenation, isomerization, hydrogenation, and cyclization/aromatization took place, which made a mixture of predominantly alkenes (Knothe et al, 2017). Doll et al (2017) calculated and fitted the activation energy of the oleic acid decarboxylation reaction, which was 249 kJ mol À1 (Knothe et al, 2017).…”
Section: Organometallic Precursor Catalystsmentioning
confidence: 99%
“…Catalytic pyrolysis at mild temperature is a promising way to save energy input, and the key is to develop an effective catalyst. Triruthenium dodecacarbonyl (TD) is an environmental‐friendly catalyst, owing to its acid‐free, non‐corrosive and non‐toxic characteristics,, and it was found that TD is active in the catalytic decarboxylation of long‐chain fatty acid from plant oil ,. In this work, TD was applied for the catalytic depolymerization of PHB, with the aim to obtain propylene at relatively mild temperature (240 °C).…”
Section: Figurementioning
confidence: 99%